All‐Printed Roll‐to‐Roll Perovskite Photovoltaics Enabled by Solution‐Processed Carbon Electrode. Issue 16 (14th March 2023) - Beynon, David; Parvazian, Ershad; Hooper, Katherine; McGettrick, James; Patidar, Rahul; Dunlop, Tom; Wei, Zhengfei; Davies, Peter; Garcia‐Rodriguez, Rodrigo; Carnie, Matt; Davies, Matthew; Watson, Trystan
Abstract: Perovskite photovoltaics have shown great promise in device efficiency but also the promise of scalability through solution‐processed manufacture. Efforts to scale perovskites have been taken through printable mesoporous scaffolds and slot die coating of flexible substrates roll‐to‐roll (R2R). However, to date there has been no demonstration of entirely R2R‐coated devices due to the lack of a compatible solution‐processable back electrode; instead,  high‐value evaporated metal contacts are employed as a post process. Here, in this study, the combination of a low‐temperature device structure and R2R‐compatible solution formulations is employed to make a fully R2R printable device architecture overcoming interlayer incompatibilities and recombination losses. Therefore, the n–i–p device structure of SnO2 /perovskite/poly(3, 4‐ethylenedioxythiophene)/carbon is employed to form an ohmic contact between a p‐type semiconductor and printable carbon electrode. In particular, the results show that the small‐scale device efficiencies of 13–14% are achieved, matching the device performance of evaporated gold electrodes. Also, this entirely R2R‐coated perovskite prototype represents a game changer, reaching over 10% (10.8) stabilized power conversion efficiency with unencapsulated long‐term stability retaining 84% of its original efficiency over 1000 h under 70% RH and 25 °C. Abstract : A new conductive carbon electrode ink is developed specifically for compatibility with a low‐temperature perovskite device stack. Filling a crucial gap in the ability to mass manufacture highly efficient perovskite photovoltaics and achieving a stabilized efficiency of 10.8%, all layers of the device stack including the electrode are roll‐to‐roll slot‐die coated.